The Long Noncoding RNA Hotair Regulates Oxidative Stress and Cardiac Myocyte Apoptosis during Ischemia-Reperfusion Injury. (12th March 2020) - Meng, Kai; Jiao, Jiao; Zhu, Rui-Rui; Wang, Bo-Yuan; Mao, Xiao-Bo; Zhong, Yu-Cheng; Zhu, Zheng-Feng; Yu, Kun-Wu; Ding, Yan; Xu, Wen-Bin; Yu, Jian; Zeng, Qiu-Tang; et al.
Abstract : Oxidative stress and subsequent cardiac myocyte apoptosis play central roles in the initiation and progression of myocardial ischemia-reperfusion (I/R) injury. Homeobox transcript antisense intergenic RNA ( Hotair ) was previously implicated in various heart diseases, yet its role in myocardial I/R injury has not been clearly demonstrated. Mice with cardiac-restricted knockdown or overexpression of Hotair were exposed to I/R surgery. H9c2 cells were cultured and subjected to hypoxia/reoxygenation (H/R) stimulation to further verify the role and underlying mechanisms of Hotair in vitro. Histological examination, molecular detection, and functional parameters were determined in vivo and in vitro. In response to I/R or H/R treatment, Hotair expression was increased in a bromodomain-containing protein 4-dependent manner. Cardiac-restricted knockdown of Hotair exacerbated, whereas Hotair overexpression prevented I/R-induced oxidative stress, cardiac myocyte apoptosis, and cardiac dysfunction. Mechanistically, we observed that Hotair exerted its beneficial effects via activating AMP-activated protein kinase alpha (AMPK α ). Further detection revealed that Hotair activated AMPK α through regulating the enhancer of zeste homolog 2/microRNA-451/calcium-binding protein 39 (EZH2/ miR-451 /Cab39) axis. We provide the evidence that endogenous lncRNA Hotair is an essential negative regulator for oxidative stress and cardiac myocyte apoptosis in myocardial I/R injury, which is dependent on AMPK α activation via the EZH2/ miR-451 /Cab39 axis.